Spatial-economic assessment of territorial organization of the Republic of Srpska (BiH) - Popović Dragana; Bomeštar Nebojša (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
The paper is based on the assumption that the root of the local development inequality is, among other factors, in inadequate territorial organization of local self-governments. The aim of this paper is to examine assessment of the territorial organization of the Republic of Srpska, with spatial and economic aspects. Due to the lack of planned spatial, functional and development model of territorial organization of local self-government in the Republic of Srpska, it is still not possible to adequately respond to the contemporary challenges of development in order to mitigate imbalance of territorial development. At the same time, the development of local communities nowadays is increasingly dependent on connectivity of the economy at the local, national and regional level. Developed local self-government is a prerequisite of active democracy and economic development, as on local level there are greatest needs and possibilities of participation of citizens in decision making process that directly affect their quality of life.